PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA (Studi Empiris Pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - Basuki Basuki (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this study is to prove empirically the effect of firm size, liquidity and investment opportunity set on earnings quality. The dependent variable in this study used the Profit Quality and the independent variable using Company Size, Liquidity, Investment Opportunity Set. The population in this study used Food and Beverage sub-sector companies listed in Indonesia Stock Exchange period 2012-2016. The results of this study indicate that firm size does not affect the quality of earnings, liquidity has a negative effect on earnings quality and investment opportunity set have a positive effect on earnings quality.Keywords : Company Size, Liquidity, Investment Opportunity Set, Profit Quality